Mercury concentrations, biomagnification and isotopic discrimination factors in two seabird species from the Humboldt Current ecosystem. (April 2022) - Le Croizier, Gaël; Point, David; Renedo, Marina; Munaron, Jean-Marie; Espinoza, Pepe; Amezcua-Martinez, Felipe; Lanco Bertrand, Sophie; Lorrain, Anne
Abstract: Assessing mercury (Hg) biomagnification requires the description of prey-predator relationships, for each species and ecosystem, usually based on carbon and nitrogen isotope analyses. Here, we analyzed two seabirds from the Humboldt Current ecosystem, the Guanay cormorant ( Phalacrocorax bougainvillii ) and the Peruvian booby ( Sula variegata ), as well as their main prey, the Peruvian anchovy ( Engraulis ringens ). We reported Hg concentrations, Hg biomagnification (BMF) and isotopic discrimination factors (Δ 13 C and Δ 15 N) in seabird whole blood. BMFs and Δ 13 C in our study (on wild birds where diet was not controlled) were similar to other piscivorous seabirds previously studied in captive settings, but Δ 15 N were lower than most captive experiments. We observed lower Hg concentrations in Humboldt seabirds compared to other oligotrophic ecosystems, possibly due to Hg biodilution in the high biomass of the first trophic levels. This work calls for a better characterization of Hg trophic dynamics in productive upwelling ecosystems. Graphical abstract: Unlabelled Image Highlights: Hg levels, biomagnification and isotopic discrimination factors in Humboldt seabirds BMFs, Δ 13 C and Δ 15 N differed from other seabirds previously studied. Lower Hg concentrations in Humboldt seabirds compared to other regions Potential Hg biodilution in the high biomass of the first trophic levels